Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan di Domino's Pizza Pamulang - Purwanti Purwanti; Ivantan Ivantan; Melvin Zakri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the partial and simultaneous influence of Service Quality and Price on Customer Satisfaction at Domino's Pizza Pamulang. Given the intense competition in the Quick Service Restaurant (QSR) sector in this sub-urban area, gaining a deep understanding of customer satisfaction drivers is crucial. This research adopts a quantitative approach using a survey method. The research population consists of all customers of Domino's Pizza Pamulang, with a sample of 100 respondents. Data were collected via questionnaires and subsequently processed and analyzed using multiple linear regression analysis. The hypothesis testing yielded significant findings: (1) Service Quality (X1) has a positive and significant influence on Customer Satisfaction (Y); (2) Price (X2) also has a positive and significant partial influence on Customer Satisfaction (Y); and (3) Service Quality and Price simultaneously proved to have a significant influence on Customer Satisfaction. The dominant contribution to customer satisfaction stems from the tangible service quality dimensions, such as delivery speed and staff friendliness, which strongly interact with customer perception of price value (value for money). The fundamental managerial implication of this study is the necessity for a strategic focus on enhancing the consistency of Service Quality at every touchpoint and ensuring competitive and high-value pricing offers to strengthen customer loyalty and satisfaction in the price-sensitive local Pamulang market.